2012
DOI: 10.2355/isijinternational.52.1463
|View full text |Cite
|
Sign up to set email alerts
|

Influence of CaO and SiO2 on the Reducibility of W^|^uuml;stite Using H2 and CO Gas

Abstract: CaO-(0-20 mass%) and SiO2-containing (0-30 mass%) wüstite ('FeO') compacts were isothermally reduced at 1 273 K under CO and H2 gas. Prior to reduction, the phase of dicalcium ferrite (Ca2Fe2O5) and fayalite (Fe2SiO4) was equilibrated with 'FeO' at 1 273 K under 50%CO/50%CO2 and identified using X-ray diffraction and scanning electron microscopy. The rate of reduction for CaO-containing 'FeO' compacts under both H2 and CO increased up to the vicinity of 2.5 mass% CaO, and then decreased with higher CaO depende… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 24 publications
2
10
0
Order By: Relevance
“…It was reported that the flux materials such as CaO and SiO 2 have influence on the reducibility of FeO affecting the interfacial chemical reaction, gaseous mass transport, and solid state diffusion of oxygen. [13] Likewise, fluxed dolomite in the present study is considered to have changed the degree of reduction of magnetite. The major components of dolomite are CaO and MgO as indicated in Table III.…”
Section: A Reduction Behavior Of Composite Pelletmentioning
confidence: 99%
See 4 more Smart Citations
“…It was reported that the flux materials such as CaO and SiO 2 have influence on the reducibility of FeO affecting the interfacial chemical reaction, gaseous mass transport, and solid state diffusion of oxygen. [13] Likewise, fluxed dolomite in the present study is considered to have changed the degree of reduction of magnetite. The major components of dolomite are CaO and MgO as indicated in Table III.…”
Section: A Reduction Behavior Of Composite Pelletmentioning
confidence: 99%
“…As Kim et al reported, CaO contents increases the reduction rate of wu¨stite by forming calcium ferrite, while SiO 2 decreases the reduction rate by forming stable fayalite compounds. [13] Thus, increased basicity in MD10 samples resulted in the faster reduction of wu¨stite as described in Eq. [7].…”
Section: A Reduction Behavior Of Composite Pelletmentioning
confidence: 99%
See 3 more Smart Citations